Makna Sertifikasi Guru terhadap Kinerja Profesional: Studi Kasus Kualitatif Berbantuan NVivo di MAN 2 Kota Batam - Sangkot Abdullah Efendi Harahap; Agus Silahudin; Ermansyah Ermansyah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Teacher certification in Indonesia is intended to enhance teachers’ professional competence, yet empirical studies show inconsistent effects on instructional quality, particularly in Islamic school contexts. This study explores how certification is perceived and enacted in professional practice at MAN 2 Batam through a qualitative case study. Five participants were involved, including three certified teachers and two vice principals. Data were gathered through in-depth interviews, classroom observations, FGDs, and document reviews, and analyzed using NVivo 15 through open and axial coding supported by thematic mapping via query and matrix functions. The findings reveal that certification fosters pedagogical reflection, strengthens administrative compliance, and expands access to professional development. However, its influence on teaching quality is not automatic and depends on institutional systems and academic supervision. The study concludes that certification should be integrated with sustained mentoring and professional learning communities to generate meaningful improvements in teaching practice and student learning.